Heat transfer modelling for timber connections in fire considering uncertainty quantification - Sulon, Darren Anthony (Stellenbosch : Stellenbosch University, 2025)
Sulon, D. 2025. Heat transfer modelling for timber connections in fire considering uncertainty quantification. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/6e44f2e3-042f-4543-a69d-898f6d59ae48